Effects of drilling fluid intrusion on the strength characteristics of layered shale - Heyuan Wang; Fuping Feng; Jianwei Zhang; Xu Han; Yuhao Zhang; Kun Zhang (Heliyon)
Drilling fluid intrusion into shale significantly impacts its strength characteristics, making related research crucial for the safe and efficient development of shale reservoirs. This paper presents an experimental approach to studying drilling fluid intrusion in shale by enhancing the conventional immersion method. The proposed method effectively simulates the actual downhole pressure conditions and the direction of intrusion, thereby aligning more closely with the real-world interactions between drilling fluids and shale during downhole operations. Using nuclear magnetic resonance (NMR) scanning, we measured the intrusion depth at layer joints while eliminating the interference from solid particles in the drilling fluid during weighing. The findings demonstrate a strong linear relationship between the depth of drilling fluid intrusion and the reduction in compressive strength. Furthermore, triaxial compression tests conducted on shale cores revealed that the strength characteristics of shale damaged along stratigraphic planes are significantly lower than those of shale affected in the main body. Notably, the intrusion of drilling fluids has a more pronounced effect on the shale damaged along the stratigraphic planes. Finally, we analyze the reaction mechanisms of amphiphilic, more lipophilic shale when exposed to various types of drilling fluids. Oil-based drilling fluids (OBDF) primarily exerts a lubricating effect on the laminar surface due to filtration fluids and hydraulic spike effects, which are predominantly physical in nature. In contrast, while the intrusion depth of water-based drilling fluids (WBDF) is somewhat less than that of OBDF, the hydration of illite surfaces induced by the filtration fluids leads to significant dispersion of the shale, with strength deterioration influenced by both physical and chemical mechanisms. The results of this research provide valuable insights for the design of drilling fluids density, performance, and fracturing development strategies in shale reservoir exploitation.